Single Exponential Smootihing (SES) Untuk Prediksi Penjualan Alat Kesehatan Pada Toko Alat Kesehatan JK Medika Prabumulih - septiya_putri_salasih Septiyaputrisalasih; zaid amin (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
In most companies in various cities, shops selling medical devices, one of which is the city of Prabumulih. Prabumulih City has a J medika medical device sales store, where the sales of the store sometimes decrease or increase sales, causing frequent shortages of stock due to the absence of predictions of the need for goods. So predictions or forecasts are needed for the sale of health equipment. This is to predict the availability of goods in the future. Forecasting is an important element in the decision-making process, the role of forecasting in various fields, such as finance, marketing, production, economics, operational research, population and so on. Forecasting activities have prediction results in the future to become one of the company's efforts in making business continuity strategy decisions. Single Exponential Smoothing method, where the Single Exponential Smoothing method explains that the data experiences instability around a stable average value. The results of predictions in the future to be one of the efforts to prepare the number of medical device items. The results of this study show the number of goods needed in 2023. Based on the results of the study, Single Exponential Smoothing resulted in a prediction of the future inventory of goods amounting to 306 medical devices.